2020
DOI: 10.1111/odi.13531
|View full text |Cite
|
Sign up to set email alerts
|

Associations between osteoporosis and risk of periodontitis: A pooled analysis of observational studies

Abstract: Background Periodontitis and osteoporosis are most popular among aging population and both conditions might be linked, even though, this suggestion still until now debated. Objectives A meta‐analysis on previous investigations has been used to evaluate the correlation between periodontitis and osteoporosis to determine whether osteoporosis is a local indicator of bone loss, or whether it is depending on or related to periodontitis causes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 55 publications
1
32
0
4
Order By: Relevance
“…Xu et al. showed that osteoporosis is closely related to the increased risk of occuring periodontitis ( 118 ). Women with postmenopausal osteoporosis treated with estrogen had a lower risk of severe periodontitis than untreated controls ( 119 ).…”
Section: Role Of Il-17a In the Relationship Between Periodontitis And...mentioning
confidence: 99%
“…Xu et al. showed that osteoporosis is closely related to the increased risk of occuring periodontitis ( 118 ). Women with postmenopausal osteoporosis treated with estrogen had a lower risk of severe periodontitis than untreated controls ( 119 ).…”
Section: Role Of Il-17a In the Relationship Between Periodontitis And...mentioning
confidence: 99%
“…Previous studies showed that OP was associated with the loss of alveolar bone (4,5), which could impact the progression of PD and was considered an independent risk factor for the prognosis of PD (6). Also, a recent meta-analysis pointed out that patients with PD were at a higher risk of developing OP (7). Evidence suggests that the two diseases are somehow related and can affect each other.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is also associated with systemic diseases, including cardiovascular diseases, Alzheimer's disease, rheumatoid arthritis, oral and colorectal carcinoma, pregnancy complications, pneumonia, and diabetes (Hajishengallis & Chavakis, 2021 ). Clinical studies have suggested that periodontitis is closely associated with osteoporosis and osteopenia, which are systemic skeletal diseases characterized by reduced bone mineral density (Passos et al., 2013 ; Xu et al., 2021 ). Compared to healthy individuals, patients with osteoporosis showed a twofold higher risk of periodontitis (Manjunath et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%